(untitled) (Revista Torreón Universitario, 2023)
The objective of this study was to evaluate the vegetative growth variables of Amaranthus cruentus L. var. Amaranteca in Managua. The cultivation was established during the months of June-September 2010, on a property located in the Ricardo Morales Avilés University Campus - UNAN Managua, the experimental unit consisted of five rows of 50 m long, with distance between plants and rows of 50 cm, 100 kg ha-1 was fertilized with NPK (12-30-10). A direct stream sowing system was used, the emergence of seedlings occurred after four days, thinning, weed control and hilling were carried out. The maximum averages in the variables were 255 cm in Height of the plant, 109 units of leaves, 29.8 cm in Length of leaf and 4.2 cm in Diameter of the stem. Significant differences (Tukey, p> 0.05) were found between Height of the plant and Number of leaves; Stem diameter and number of leaves; and Stem diameter and size of leaves.